Mantle convection in the earth and planets - Schubert, Gerald (Cambridge University Press, 2001)
This book is a comprehensive and up-to-date synthesis of all aspects of mantle convection. It is suitable as a graduate textbook in geophysics and planetary physics, and as an invaluable review for researchers in the broad fields of the earth and planetary sciences.